Spatiotemporal dynamics and determinants of human-land relationships in urbanization: a Yangtze River Economic Belt case study - Zhou, Laiyou; Huang, Yixin (Frontiers in Environmental Science, 2024)
The harmonious advancement of human-land dynamics is essential for developing people-centric urbanization strategies. Investigating the interplay between demographic urbanization and land development through a spatiotemporal lens holds significant practical value. This study examines 110 prefecture-level cities within the Yangtze River Economic Belt, employing an integrative methodology that includes a coupled coordination model, exploratory spatial data analysis, and a fixed effects model to probe the symbiotic relationship between population urbanization and land urbanization, as well as the determinants of their interconnectivity. The findings reveal (1) a progression in the coupled coordination level of demographic and land urbanization within the region, rising from 0.1 to 0.88 between 2006 and 2021, signifying a shift from pronounced disequilibrium to a state of heightened coordination; (2) a spatial gradient in the coupled coordination level, diminishing from downstream to upstream areas, manifesting as a "high-east, low-west" distribution pattern, with both overall and regional disparities in coordination experiencing a decline; and (3) that multiple factors influence the coupled coordination level, encompassing government administration, capital investment in fixed assets, economic growth, and investment in education. This study advocates for surmounting institutional and policy impediments to transregional coordination, fostering the unimpeded exchange and judicious distribution of diverse resources, and thus facilitating the integrated evolution of human-land dynamics within the Yangtze River Economic Belt.